MUZAKIR MANAF’S POLITICAL STRATEGY IN THE 2024 ACEH GUBERNATORIAL ELECTION: A SYMBIOTIC NARRATIVE OF ISLAM AND ACEHNESE IDENTITY - Ahmad Winaldi; Hasyimsyah Nasution; Syukri Syukri (UNIVERSITAS PAKUAN, 2025)
This study analyzes the political strategy of Muzakir Manaf in the 2024 Aceh Gubernatorial Election, focusing on his use of identity politics, digital adaptation, and principles of Islamic political thought. Employing a qualitative method with a case study approach, data were gathered through in-depth interviews, documentary analysis, and limited observation. The findings reveal that Muzakir Manaf’s political maneuvering was predicated on a blend of his party’s structural power, a historical narrative rooted in Acehnese symbolism and struggle, and a symbiotic strategy linking political action to Islamic values. This approach successfully forged an emotional connection with his traditional voter base and the ulama (Islamic scholars), thereby strengthening an image of leadership grounded in morality. However, his campaign team demonstrated a significant weakness in its digital communication strategy, characterized by a non-confrontational response to emergent issues and disinformation, which risked damaging his credibility. The study also uncovers a shifting orientation among young voters, who are increasingly rational and demand moral consistency and tangible performance over mere symbolism. Overall, this research contributes to the understanding of political leadership adaptation in post-conflict Aceh. It underscores the importance of balancing historical legacies with inclusive contemporary political demands and the necessity for leaders to adapt to an increasingly critical and digitally savvy electorate.